2005
DOI: 10.1074/jbc.m413627200
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4 Gene Disruption in Mice Reduces Brain Swelling and Mortality in Pneumococcal Meningitis

Abstract: The astroglial water channel aquaporin-4 (AQP4) facilitates water movement into and out of brain parenchyma. To investigate the role of AQP4 in meningitisinduced brain edema, Streptococcus pneumoniae was injected into cerebrospinal fluid (CSF) in wild type and AQP4 null mice. AQP4-deficient mice had remarkably lower intracranial pressure (9 ؎ 1 versus 25 ؎ 5 cm H 2 O) and brain water accumulation (2 ؎ 1 versus 9 ؎ 1 l) at 30 h, and improved survival (80 versus 0% survival) at 60 h, through comparable CSF bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
195
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(207 citation statements)
references
References 49 publications
7
195
4
1
Order By: Relevance
“…Overexpression of AQP4 may cause an increased propensity for cerebral edema. Experiments using AQP4 knockout mice revealed that AQP4 deletion offered protection from cytotoxic brain edema (Papadopoulos et al 2005) and vasogenic (noncellular) brain edema (Papadopoulos et al 2004). Our laboratory has observed a significant decrease in AQP4 in the cerebellum of patients with autism (Fatemi et al unpublished observations).…”
Section: Discussionmentioning
confidence: 91%
“…Overexpression of AQP4 may cause an increased propensity for cerebral edema. Experiments using AQP4 knockout mice revealed that AQP4 deletion offered protection from cytotoxic brain edema (Papadopoulos et al 2005) and vasogenic (noncellular) brain edema (Papadopoulos et al 2004). Our laboratory has observed a significant decrease in AQP4 in the cerebellum of patients with autism (Fatemi et al unpublished observations).…”
Section: Discussionmentioning
confidence: 91%
“…Manipulation of AQP abundance may therefore provide novel methods for treating specific diseases. For example, AQP4 knockout mice show an increased protection and reduced accumulation of water in the brain in models of ischemic stroke, cerebral injury and meningitis (Manley et al, 2000, Papadopoulos andVerkman, 2005). The opposite is the case for hydrocephalus and vasogenic oedema, where AQP4 null mice show greater water accumulation in the brain and a worse clinical outcome (Papadopoulos et al, 2004).…”
Section: Conclusion: Implications For Disease Therapiesmentioning
confidence: 99%
“…Phenotype analysis of AQP4 knockout mice has revealed the involvement of AQP4 in water movement into and out of the brain, in neuroexcitation phenomena such as seizure activity and cortical spreading depression, and in glial cell migration 1 . AQP4 knockout mice showed improved survival compared to control wildtype mice in models of cytotoxic brain edema, including water intoxication, ischemic stroke and bacterial meningitis 2,3 . Recently, greatly improved neurological outcome was found in AQP4 knockout mice following spinal cord injury, which was associated with reduced spinal cord swelling and nerve cell protection 4 .…”
Section: Introductionmentioning
confidence: 99%